ChemInform Abstract: In situ Preactivation Strategies for the Expeditious Synthesis of Oligosaccharides: A Review. Issue 48 (2nd December 2014) - Bouhall, Samantha K.; Sucheck, Steven J.
Abstract Review: 74 refs.